PULMONARY FUNCTION CHANGES IN SANITARY WORKERS OF KANCHIPURAM POPULATION - Pappaiya, Muninathan; Vadivel, Kamalakannan; Chelliah, Selvakumar (Asian Journal of Pharmaceutical and Clinical Research, 2023)
Objectives: The main objective of this study is to evaluate the respiratory function of sanitary workers as they are most exposed to environmental air pollutants. Methods: The study was done among sanitary workers of Kanchipuram Municipality, Tamil Nadu, with 190 subjects, who were divided into two groups such as Group I and Group II. Group I with 96 sanitary workers and Group II with 94 as the control group with age- and morphometric-matched subjects. The subjects involved are both gender with the age group between 20 and 60 years. Various functional parameters, namely FVC, FEV1, FVC/ FEV1, FEF 25%, FEF50%, and FEF75%, were done using RMS Helios 3.1.37 in the Physiology Department, Meenakshi Medical College and Research Institute. Institutional Ethical Committee approval was obtained from Institutional Human Ethical Committee. Results: The pulmonary findings showed a significant decrease in FVC, FEV1, FVC/FEV1, FEF 25%, FEF50%, and FEF75% when compared to the control group. Conclusion: The sanitary workers showed a significant decrease in the pulmonary function tests as they were exposed to a variety of solid waste particles which might have caused inflammatory and immunological responses with the small and large airways of the respiratory tract.